PDMS anatomical realistic models for hemodynamic studies using rapid prototyping technology - Queijo, Luis (2012)
The main purpose of this work is to investigate a simple way of making polydimensiloxane (PDMS) anatomically artery models such as a carotid arteries with and without aneurysm. By using a human carotid computerized tomography (TC) it was possible to develop 3D anatomical models through the application of a rapid prototyping (RP) technique, known as tridimensional printing (TDP). By combining the TDP with a PDMS casting technique we were able to obtain at the end an anatomically transparent model of a human carotid artery made by a silicon elastomer, i.e. PDMS. We believe that this combination is a promising technique to perform more realistic in vitro blood studies through anatomical models and consequently improve our current understanding of the origin and development of cardiovascular diseases.